New highly lodging resistant winter rye variety ‘Evrika’ - N. A. Petrovtseva (Зерновое хозяйство России, 2022)
The development of highly productive short-stemmed winter rye varieties that do not lodge under intensive cultivation technologies is one of the main breeding tasks. The current paper has presented the study results of a new winter rye variety ‘Evrika’ according to the main economically valuable traits in the North-West region of the Russian Federation. The variety was developed by the Leningrad Scientific Research Institute of Agriculture «Belogorka» based on complex hybridization of the varieties ‘Bylina’ and ‘Volkhov’ from the North-West region with varieties of Russian and foreign selection, among which the varieties ‘Alfa’, ‘Antares’, ‘Saratovskaya 5’ and ‘Otello’ made the most significant contribution. The breeding feature of the new variety is the use of donors of such types of a short stem trait as dominant-monogenic and recessive-polygenic. The study was carried out for three years (2019–2021) in the nurseries of Competitive Variety Testing on the fields of the institute in the Gatchinsky district of the Leningrad region. The purpose of the study was to identify the biological and economically valuable traits of a new winter rye variety ‘Evrika’. According to the study results, the variety ‘Evrika’ belongs to the group of semi-short-stem varieties with a mean plant height of 125.5 cm. The variety showed good winter tolerance (8–9 points) and high resistance to lodging (8–9 points). The mean grain productivity of the new variety through the years of research was 5.0 t/ha, with the maximum of 7.4 t/ha, which exceeded the productivity of the standard variety ‘Volkhov’ on 0.9 t/ha (19.5 %) and 2.1 t/ha (39.6 %), respectively. The mean green mass productivity was 25.8 t/ha, exceeding the standard’s productivity on 3.5 t/ha (15.7 %). The index of 1000-grain weight of a new variety during the period varied from 34.5 to 39.0 g, depending on the climatic conditions of the year. According to the study results, the variety ‘Evrika’ was highly appreciated, having successfully passed the State Variety Testing. In 2021 the variety was included in the State List of Breeding Achievements in the North-West Region of the Russian Federation.